2019
DOI: 10.3390/app9152974
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Physiological Scale of Vocal Fold Agent-Based Models of Surgical Injury and Repair: Sensitivity Analysis, Calibration and Verification

Abstract: Agent based models (ABM) were developed to numerically simulate the biological response to surgical vocal fold injury and repair at the physiological level. This study aimed to improve the representation of existing ABM through a combination of empirical and computational experiments. Empirical data of vocal fold cell populations including neutrophils, macrophages and fibroblasts were obtained using flow cytometry up to four weeks following surgical injury. Random Forests were used as a sensitivity analysis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 107 publications
1
11
0
Order By: Relevance
“…However, to effectively resolve inflammation and promote healing, M2 polarization would be required to succeed M1 as the dominant local population of macrophages. Such speculations of vocal fold macrophage polarizations were observed in the animal study [44] and later confirmed by Kishimoto's research team. [40] Also, fibroblastÀmyofibroblast transdifferentiation was observed in the same animal study, emulating in vitro studies, subjecting vocal fold fibroblasts to growth factor stimulations from Thibeault's and Kishimoto's research teams, respectively.…”
Section: Immunological Profile Of the Vocal Foldssupporting
confidence: 56%
See 2 more Smart Citations
“…However, to effectively resolve inflammation and promote healing, M2 polarization would be required to succeed M1 as the dominant local population of macrophages. Such speculations of vocal fold macrophage polarizations were observed in the animal study [44] and later confirmed by Kishimoto's research team. [40] Also, fibroblastÀmyofibroblast transdifferentiation was observed in the same animal study, emulating in vitro studies, subjecting vocal fold fibroblasts to growth factor stimulations from Thibeault's and Kishimoto's research teams, respectively.…”
Section: Immunological Profile Of the Vocal Foldssupporting
confidence: 56%
“…Fibroblasts were abundantly populated across all layers of the lamina propria, with the highest number found in the deep lamina propria (DLP). [38] Upon injury to the lamina propria, rapid neutrophil and monocyte recruitment from peripheral capillaries occurs, as demonstrated across experimental models of mice, [40] rats, [41][42][43][44] rabbits, [45] and pigs. [46,47] Li-Jessen's team applied multicolor flow cytometry to characterize temporal trajectories of neutrophils…”
Section: Immunological Profile Of the Vocal Foldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, VFFs represent the most abundant cell type found within the lamina propria where they serve to maintain and repair the vocal fold mucosa 22‐24 . VFFs have been recognized for their mechanosensitive and immunomodulatory properties including their ability to suppress pro‐inflammatory cytokine production 25‐28 . Fibroblast‐like cells have been suggested to have some behavioral capacities similar to innate immune cells and also play a role in inflammatory resolution 29 .…”
Section: Introductionmentioning
confidence: 99%
“…GSEA results showed that the inhibitors of PRL influenced by wounding were mainly involved in interferon-gamma signaling, epithelial cell and endothelial cell proliferation, wound healing and growth factor responds, which were suggested to associate with VF wound healing [19][20][21][22]. These results indicated that VF wound might up-regulate these pathways that influence the secretion of prolactin.…”
mentioning
confidence: 99%